Canadian Anthropologists, the First Nations and Canada’s Self-Image at the Millennium - Darnell, Regna (Anthropologica, 2022)
Canadian anthropology attains its unique character by virtue of the discipline’s embedding in debates over Canadian national identity and unity. This paper explores Canadian national identity in relation to the First Nations as a third founding force dissolving the binary of French vs. English. First Nations values, it is argued, must be incorporated within the reflexive self-image of Canada, both in interests of social justice for the First Nations and as part of what makes Canada a richly complex intersection of standpoints (ethnic, class, regional, etc.). As a result of this social and cultural complexity, Canada is ideally poised to meet the challenges of globalization and Canadian anthropologists are well-situated to mediate and explicate this process.